Sneddon’s syndrome: A case report with diagnostic approach and imaging review - Soukaina Beyyato, MD; Zineb Yammouri, MD; Hajar Ouazzani, PhD; Ismail Chaouche, PhD; Amal Akammar, PhD; Nizar El Bouardi, PhD; Meriem Haloua, PhD; Moulay Youssef Alaoui Lamrani, PhD; Mustapha Maaroufi, PhD; Meryem Boubbou, PhD; Badreeddine Alami, PhD (Radiology Case Reports)
Sneddon’s syndrome is a rare thrombotic vasculopathy characterized by the association of livedo racemosa and ischemic cerebrovascular events, typically affecting young to middle-aged women. We report the case of a 41-year-old woman who presented with sudden right-sided hemiparesis, expressive aphasia, and a history of livedo racemosa. MRI revealed bilateral ischemic lesions and cortical atrophy, while autoimmune and thrombophilia workups were negative. This case emphasizes the importance of considering Sneddon’s syndrome in young patients with recurrent strokes and livedo racemosa, and highlights the diagnostic value of MRI combined with clinical evaluation.